Review of Joachim Weber (ed.), Handbook on Geopolitics and Security in the Arctic: The High North Between Cooperation and Confrontation - Tsiouvalas, Apostolos (Arctic Review on Law and Politics, 2021)
Handbook on Geopolitics and Security in the Arctic: The High North Between Cooperation and Confrontation, edited by Joachim Weber, is part of the Springer series Frontiers in International Relations. Published in 2020, the anthology comes at a turbulent time in Arctic geopolitics, when the traditional supremacy of the Arctic littoral states has started to be challenged by lurking interests of non-Arctic stakeholders, and global anthropogenic challenges, such as climate change, keep raising questions as to the future of security and geopolitical balance in the region. The handbook comprises a compelling read with diverse areas of discussion that give an insightful exploration of the most pressing issues relevant to Arctic geopolitics. The multidisciplinarity of approaches employed in this volume and the variety of relevant topics covered have the potential to mark a turning point in international scholarship on geopolitical studies.